COVD-30. A SNAPSHOT OF THE IMPACT OF COVID-19 ON PATIENTS WITH NERVOUS SYSTEM TUMORS. (9th November 2020) - Aaroe, Ashley; ,; Harrison, Rebecca; Majd, Nazanin; O'Brien, Barbara; Weathers, Shiao-Pei; Loghin, Monica; Kamiya-Matsuoka, Carlos; Yung, W K Alfred; de Groot, John; Woodman, Karin
Abstract: BACKGROUND: The impact of COVID-19 on patients with nervous system tumors is not known. This population is often immunosuppressed, susceptible to neurological complications, and requiring of frequent cancer care, all of which may confer vulnerability to poorer outcomes after infection. METHODS: Clinical data were obtained from structured electronic medical record elements, clinical note text and laboratory RESULTS: Each source was identified, integrated and analyzed using the Palantir Foundry platform (Syntropy), part of the Context Engine Data Management System through the MD Anderson Cancer Center (MDACC) IRB approved D3CODE initiative. The population of interest was patients diagnosed with COVID-19 who had been seen at the Brain and Spine Center for nervous system tumors. RESULTS: 8, 177 ambulatory patients were seen at the Brain and Spine Center from 3/1/20–9/1/20. COVID status was known for 1, 753 (21%). Sixty-one (0.7%) were COVID-19 positive. Of these, 17 had primary nervous system tumors. Seven (41%) were treated in the emergency department or hospital for infection. Two were symptomatic but did not require further care. Eight were asymptomatic. Nine (53%) had alterations in cancer management within one week of COVID-19 diagnosis – delayed surgery (3), delayed/interrupted chemotherapy (2), delayed/interrupted radiation (2), cancer treatment discontinued (2). Eight patients (47%) had no clear impact of infection on their cancer treatment, three were on surveillance. Three (18%) unique patients had neurological symptoms attributed to/exacerbated by COVID-19 – encephalopathy (2), seizure (2), stroke (1). CONCLUSION: No deleterious effects of alterations in cancer management after COVID-19 infection have been identified thus far, though longitudinal follow up is warranted. Our results suggest that COVID-19 infection frequently incurs medical complications or alterations in cancer treatment. The potential impacts of COVID-19 on our vulnerable neuro-oncology patient population should be further explored, and attention to these potential implications for our patients is warranted by treating clinicians.